SISTEM PEMBERIAN UPAH TERHADAP KINERJA KARYAWAN KONVEKSI DAYAT DITINJAU DALAM PERSPEKTIF EKONOMI ISLAM - Nurhasiah; Muflihah, Hani; Yumsinah, Siti (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2022)
Islamic Shari'at emphasizes that wages are the right of people who have worked and are obliged to provide wages in a fair way and in accordance with what has been done. The aim of the research is to dig deeper into the wage system in terms of Islamic economics. This research uses a quantitative approach which is a method to test certain theories by examining the relationship between variables. The data collection technique used was through interviews, questionnaires which were carried out face-to-face and filled in directly by the informants. The wage system on employee performance has a system influence, namely: the statistical results of the t test, with a tcount value of 5.73 greater than the ttable of 1.684 with a significant value of 0.000 less than 0.05. Which means that there is influence on the wage system. Furthermore, the magnitude of the influence of the wage system on the performance of Dayat convection employees is: It can be seen from the results of the hypothesis test on the wage variable with a significant value of 0.360 So thus Ha is accepted and H0 is rejected.